2012
DOI: 10.1111/j.1601-0825.2012.01960.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic characterization and distribution of dendritic cells in odontogenic cystic lesions

Abstract: Oral Diseases (2012) 19, 85–91 Objective:  To analyze the expression and distribution patterns of mature dendritic cells (mDCs) and immature DCs (imDCs) in radicular cysts (RCs), dentigerous cysts (DtCs), and keratocystic odontogenic tumors (KCOTs). Materials and methods:  Forty‐nine odontogenic cystic lesions (OCLs) (RCs, n = 20; DtCs, n = 15; KCOTs, n = 14) were assessed using the following markers: S100, CD1a and CD207 for imDCs; and CD83 for mDCs. Results:  Almost all cases were S100, CD1a, and CD207 posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…As previously commented, LCs are a distinct subtype of imDCs (S100+, CD1a+, and CD207+) which, after antigen capture and subsequent displacement to regional lymph nodes, differentiate into mDCs; the latter are characterized by expression of CD83 and CD208. 15,21,27,39,40,41 In the current study, CD208 expression has been observed, preferentially on gingival lamina propria, indicating that DC maturation in situ occurs, corroborating the Jotwani et al 27 study. Moreover, interestingly, it was visualized focal intraepithelial location of CD208+ cells, which appear to correspond to LCs (Fig.…”
Section: Clinical and Demographic Characteristics Of Periodontal Disesupporting
confidence: 91%
See 4 more Smart Citations
“…As previously commented, LCs are a distinct subtype of imDCs (S100+, CD1a+, and CD207+) which, after antigen capture and subsequent displacement to regional lymph nodes, differentiate into mDCs; the latter are characterized by expression of CD83 and CD208. 15,21,27,39,40,41 In the current study, CD208 expression has been observed, preferentially on gingival lamina propria, indicating that DC maturation in situ occurs, corroborating the Jotwani et al 27 study. Moreover, interestingly, it was visualized focal intraepithelial location of CD208+ cells, which appear to correspond to LCs (Fig.…”
Section: Clinical and Demographic Characteristics Of Periodontal Disesupporting
confidence: 91%
“…CD83 is a member of the immunoglobulin superfamily, which is upregulated during the maturation of DCs 15 , 44 . Moreover, it is known that CD83 may be expressed by monocytes and macrophages, weakly by germinal center lymphocytes, and at low levels by B‐ and T‐cell populations 45 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations